Identifying and ranking of strategies to implement green supply chain management in Indian manufacturing industry using Analytical Hierarchy Process - Sunil Luthra (Journal of Industrial Engineering and Management, 2013)
Purpose – The study aims to identify and rank the major strategies that help achieve successful implementation of Green Supply Chain Management (GSCM) in Indian manufacturing industry. Design/methodology/approach – Strategies to implement GSCM have been identified thorough extensive literature review and then experts’ opinion is sought for categorizing them into four representative dimensions which are then ranked using Analytic Hierarchy Process (AHP). Findings – The study categorizes the GSCM implementation strategies into four dimensions - Non members of supply chain, downward stream supply chain Members, Organizational members of supply chain and upward stream supply chain members. These dimensions are found to play an important role in greening the supply chains enabling the practicing firms achieve enhanced operational performances. Research limitations/implications- AHP is used for ranking the GSCM implementation strategies in Indian manufacturing scenario. The pair-wise comparisons are made on the basis of the opinion of the experts drawn from academia and industry. As is natural, opinions of experts may not always be free from bias or prejudices. Moreover, the study relied more on the GSCM practices literature in developed nations as only limited literature related to the undertaken work in the Indian context was available. Practical implications – This paper may play important role in understanding various strategies and ranking them in order of importance. This facilitates firms prioritize different actions for achieving high GSCM performances in Indian manufacturing industry. Strategic implementation of green supply chain management will help Indian manufacturing enterprises enjoy cost and efficiency benefits. Originality/value – GSCM is a relatively new topic for majority of Indian manufacturing industries. This work is likely to help GSCM practitioners select suitable strategies in consonance with the government regulations and customers’ requirements.